The behavior of Tapered High Strength Concrete Filled Steel Tube (CFST) Column connected to Encased Steel Reinforced Concrete Composite (SRC) Column - Abdelhamid Azzazy, Yasser (2020)
The use of Convectional Concrete Column is often limited in high-rise Buildings due to the constraint from the architects on increasing size of the columns, so the composite columns provide appropriate solution to satisfy the architect and the Client with smaller column size. Nowadays, Composite Columns have been widely developed in the construction of the high-rise buildings, long span structures, and bridges. Composite columns have two main types, encased composite columns (SRC) and concrete filled steel tube columns (CFST). This research is focusing on the behavior of a tapered concrete filled steel tube column (CFST) connected to encased composite column (SRC). The purpose of having two different sections along the column height is to enhance the flexure resistance of the column at the top edge by introducing CFST element, while the lower part is modeled as SRC element and it is mainly subjected to axial compression with significant reduction in bending moments compared to the top part of the column. The behavior of the tapered CFST column connected to SRC column has been studied using two main different parameters. The first parameter is the type of loading, such as pure axial compression, axial compression and uni-axial bending, and axial compression and bi-axial bending. The second parameter is the concrete strength, with different concrete strengths ranging from C40MPa to C70MPa. Both parameters have been carefully considered in the analysis of the composite column. The steel section used in the research design model has a yield strength of 355MPa. The steel reinforcement used in the model has a yield strength of 500MPa. The column has been modeled using 3D-Fiber (Solid) Finite Element Method. The cross sectional of the columns has been divided into tiny fiber (solid) elements. The advantage of using a fiber (solid) element is easy to assign the tiny element as concrete or steel, even stiffeners plates have been modeled by adopting the fiber element methodology. The maximum size of the fiber (solid) element is (10mm x 10mm) which warrant more accurate results in terms of stress and strain. The vertical rebar was ignored from the 3D Fiber Model. The stresses and strains extracted from the 3D-FE models have been compared to the simplified formulas adopted by EUROCODE-4 and American Standards AISC / ANCI . The research illustrates the load path and stress / strain distribution through different structural elements connected to each other under deferent type of loading. The results demonstrate that the 3D-FEM displays some differences in the composite section capacity under different type of loading compared to the simplified formula adopted by Eurocode and AISC/ANCI. The stress and strain distribution demonstrate a smooth transition between CFST element and SRC element with local stress concertation on the concrete and steel at the interface between CFST element and SRC element. The concentration in the stresses is not considered in the simplified formula by the standards codes, so it should be carefully considered in the section capacity.